2003
DOI: 10.1152/ajpregu.00610.2002
|View full text |Cite
|
Sign up to set email alerts
|

Hyperleptinemia and reduced TNF-α secretion cause resistance of db/db mice to endotoxin

Abstract: Madiehe, Abram M., Tiffany D. Mitchell, and Ruth B. S. Harris. Hyperleptinemia and reduced TNF-␣ secretion cause resistance of db/db mice to endotoxin. Am J Physiol Regul Integr Comp Physiol 284: R763-R770, 2003; 10.1152/ ajpregu.00610.2002-Leptin deficiency in ob/ob mice increases susceptibility to endotoxic shock, whereas leptin pretreatment protects them against LPS-induced lethality. Lack of the long-form leptin receptor (Ob-Rb) in db/db mice causes resistance. We tested the effects of LPS in C57BL/6J db… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 38 publications
2
27
0
Order By: Relevance
“…Corticosteroids induce apoptosis of immature thymocytes and play a critical role in acute thymic involution (28). LPS activates the HPA axis to elevate systemic corticosteroids (26,29). Leptin in turn has been shown to have a negative feedback effect on the HPA axis by inhibiting the corticotropinreleasing hormone protein (25).…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroids induce apoptosis of immature thymocytes and play a critical role in acute thymic involution (28). LPS activates the HPA axis to elevate systemic corticosteroids (26,29). Leptin in turn has been shown to have a negative feedback effect on the HPA axis by inhibiting the corticotropinreleasing hormone protein (25).…”
Section: Discussionmentioning
confidence: 99%
“…N in these animals did not result in any change in weight gain ( Figure 1B), body composition ( Figure 2, A and B), resting metabolic rate ( Figure 3A), or efficiency of food consumption ( Figure 3B). Recent studies suggested that db/db mice resisted LPS-induced anorexia by reducing TNF-α secretion (27). Thus, leptin may have an important role in the regulation of appetite, body composition, and metabolic rate in uremia.…”
Section: Tablementioning
confidence: 99%
“…Leptin-deficient mice (ob/ob) seem to be unaffected [14] or protected [15] from the deleterious effects of endotoxin. On the other hand, Gultekin et al [16] demonstrated that exogenous leptin may be protective role in cerulein-induced acute pancreatitis associated to ALI, and Dong et al [17] showed that leptin-deficient ob/ob mice were more susceptible to LPS-related lethality than lean mice.…”
Section: Introductionmentioning
confidence: 99%